Nonpharmacological Interventions for Pain in Patients with Temporomandibular Joint Disorders: A Systematic Review - Argueta-Figueroa, Liliana; Flores-Mejía, Luis Angel; Ávila-Curiel, Beatriz Xóchitl; Flores-Ferreyra, Blanca Irma; Torres-Rosas, Rafael (European Journal of Dentistry, 2022)
This systematic review aimed to compare the efficacy of nonpharmacological therapies for painful temporomandibular joint disorders. The protocol was registered on International Prospective Register of Systematic Reviews (PROSPERO) database (CRD42020171364). The search was performed on the electronic databases PubMed, Google Scholar, Clinical Trials, and Web of Science. The eligibility criteria were randomized controlled trials in patients diagnosed with painful temporomandibular joint disorders comparing the pain relief between conventional treatment and nonpharmacological therapies such as acupuncture, physiotherapy, low-level laser, and massage. Fourteen articles were included in this review. At the overall bias of the studies included, 71.42% exhibited some concerns and 28.57% had high risk. The efficacy of nonpharmacological interventions was found to be moderate in the short term and variable in the long term for pain reduction in patients with temporomandibular joint disorders. The evidence pointed out that acupuncture, laser therapy, and physiotherapy are potentially useful interventions for pain relief in patients with temporomandibular joint disorders. However, there is a lack of consistency and short-term follow-up in the studies to determine the lasting of such effect.
Keywords: dentistry; physiotherapy; complementary; pain; temporomandibular joint